Time-consistent carbon pricing - Olga Chiappinelli; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
In this paper we show that carbon pricing is subject to time-inconsistency and we investigate solutions to improve on the problem and restore the incentive for the private sector to invest in low-carbon innovation. We show that a superior price-investment equilibrium can be sustained in the long-term, if the policy-maker is enough forward looking and allowed to build reputation. In the short-term, time-inconsistency can be alleviated by complementing carbon pricing with project-based carbon price guarantees.
Additional information: Newer version published at DP 1859 (2020). Please cite the new version: http://hdl.handle.net/10419/218980; More recent version: http://hdl.handle.net/10419/218980
Keywords: C73; L51; O31; Q58; 330; Carbon pricing; Time-inconsistency; Low-carbon innovation; Environmental regulation; Repeated games; Carbon contracts